Stock Returns and the Volatility of Liquidity - Pereira, João Pedro; Zhang, Harold H. (Journal of Financial and Quantitative Analysis, 2010)
Abstract This paper offers a rational explanation for the puzzling empirical fact that stock returns decrease with an increase in the volatility of liquidity. We model liquidity as a stochastic price impact process and define the liquidity premium as the additional return necessary to compensate a multiperiod investor for the adverse price impact of trading. The model demonstrates that a fully rational, utility maximizing, risk-averse investor can take advantage of time-varying liquidity by adapting his trades to the state of liquidity. We provide new empirical evidence supportive of the model.